Alkaloids from Zephyranthes robustaBaker and Their Acetylcholinesterase‐ and Butyrylcholinesterase‐Inhibitory Activity. Issue 6 (18th June 2013) - Kulhánková, Andrea; Cahlíková, Lucie; Novák, Zdeněk; Macáková, Kateřina; Kuneš, Jiří; Opletal, Lubomír
Abstract The bulbs of Zephyranthes robusta (Amaryllidaceae) have been extensively analyzed for their chemical constituents, resulting in the isolation of 13 alkaloids. The chemical structures of the isolated compounds were elucidated by mass‐spectrometric, and 1D‐ and 2D‐NMR spectroscopic experiments. The complete NMR assignments were achieved for hippeastidine. All isolated alkaloids were evaluated for their erythrocytic acetylcholinesterase and serum butyrylcholinesterase inhibitory activities using the Ellman's method. Significant acetylcholinesterase inhibition activity was exhibited by 8‐O‐demethylmaritidine (IC50(HuAChE) 28.0±0.9 μM).